Deriving a Narrative Infrastructure from Community Stories in Famagusta Walled City - Winn, Jason Murray (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
[Abstract Not Available]
Master of Science in Urban Design. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2019. Supervisor: Assist. Prof. Dr. Ceren Boğaç.
Keywords: Urban Design; City planning-Environmental aspects-Sustainable development-Historic Cities-Famagusta (Cyprus, North); Planning-Environmental policy-Cyprus, North; Cities-Environmental aspects-Urban policy; City planning-Community Stories; Urban Change-Historic preservation-Famagusta Walled City-Cyprus (Turkish Republic of Northern Cyprus, 1983-); Community Stories-Famagusta Walled City; Cities and Towns; Heritage Preservation; Urban Transformation; Urban History; Social History; Urban Heritage; Public History; Urban Conservation; Historic Preservation; Historic Environment; Urban Regeneration; Narrative; Oral History; Storytelling; Urban Planning; Urban Design; Famagusta